UPAYA PENINGKATAN KESIAPSIAGAAN BENCANA MELALUI PELATIHAN BERBASIS PENDEKATAN PARTISIPATIF MASYARAKAT DI BANJAR KRISNANTARA, DESA TIBUBENENG - I Made Dwie Pradnya Susila; Ida Ayu Agung Laksmi; Made Adi Wahyu Udaksana (Synergy and Society Service, 2023)
The Community-Based Disaster Preparedness Program carries out steps to empower community capacity so that they are able to reduce the level of risk and impact of disasters that arise in disaster management and emergency response. Communities living in disaster-prone areas can play a direct role as helpers. One of the first steps is to provide training to communities in disaster-prone areas. Communities living in disaster-prone areas must increase their capacity, including those in Banjar Krisnantara, Tibubeneng Village. The area of Banjar Krisnantara, Tibubeneng Village is one of the areas in Badung Regency with densely populated settlements and is geographically a vulnerable area to floods and tsunamis. Therefore, community-based disaster preparedness training is urgently needed through a participatory approach in Banjar Krisnantara, Tibubeneng Village as part of an effort to empower people who are vulnerable to safety and health issues due to disasters. This activity involves 2 lecturer members who have eligibility qualifications and 3 students whose activities are recognized with credits in accordance with the Independent Learning principles. This activity was carried out from 11-27 June 2023 which was divided into 3 stages, namely the orientation stage, the implementation stage, and the evaluation stage. The results of effective activities in increasing community preparedness in Banjar Krisnantara, Tibubeneng Village with all specific objectives achieved include the existence of a safe gathering point, increasing the level of community preparedness and the emergence of the forerunner to the formation of a Sibat team by all heads of families in Banjar Krisnantara who participated in the training.